Ethnobotany of suweg, Amorphophallus paeoniifolius: Utilization and cultivation in West Java, Indonesia - ASEP ZAINAL MUTAQIN; DENNY KURNIADIE; JOHAN ISKANDAR; MOHAMAD NURZAMAN; Ruhyat Partasasmita (Society for Indonesian Biodiversity, 2020)
Abstract. Mutaqin AZ, Kurniadie D, Iskandar J, Nurzaman M, Partasasmita R. 2020. Ethnobotany of suweg, Amorphophallus paeoniifolius: Utilization and cultivation in West Java, Indonesia. Biodiversitas 21: 1635-1644. Amorphophallus paeoniifolius (Dennst.) Nicolson, locally known as suweg, is a bulbous plant that has many benefits, but has not been cultivated as intensively as other species from the Araceae family. Suweg grows scattered in various rural areas in Indonesia, including West Java. Some suweg plants are cultivated by villagers, while the others grow wildly in forested areas. Suweg is commonly cultivated in several types of agroecosystems, such as home gardens (pekarangan) and gardens (kebun), using traditional ecological knowledge inherited from generation to generation. This study aims to investigate the utilization and cultivation of suweg by a community in Cisoka Village, Cikijing Sub-district, Majalengka District, West Java. This study used a qualitative method using ethnobotany approach, i.e. an emic analysis of the perception and local knowledge of community on suweg, and then validated using scientific or ethical knowledge. Field data collection was done by observation and semi-structured interviews with key informants chosen purposively considered having expertise and knowledge about suweg. The results showed that suweg has long been cultivated or growing naturally in Cisoka Village. The species has been culturally utilized by the rural community as additional food sources of carbohydrates, fish feed, and traditional ceremonies. However, the use of traditional ceremonies has been lost its importance. Suweg is generally used by the elderly, with certain groups, such as rural fish farmers and some younger age groups or children who like suweg. The rural people of Cisoka Village also mentioned that suweg was not cultivated as intensively as other. This is partly because it is considered not to have a high economic value as other agricultural commodities.